HUBUNGAN PENDIDIKAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MEUREUBO TAHUN 2024 - Salmaza; Iskandar, Wardah; Eka Putri, Suci; Muliadi, Teuku (Jurnal Biogenerasi, 2024)
The aim of this research is to look at the relationship between education, knowledge and family support with exclusive breastfeeding behavior in the working area of ​​the Meureubo Health Center in 2024. This research method uses a quantitative approach with a cross sectional design. The population in this study were all mothers who had babies aged 6-12 months. Respondents in the study were 123 who had babies aged 6-12 months. The instrument used was a questionnaire. Data analysis used chi-square. The results of the research show that there is a significant relationship between education and exclusive breastfeeding behavior in the Meurebo Community Health Center working area with a p value of 0.029 < 0.05. There is a significant relationship between knowledge and exclusive breastfeeding behavior in the Meurebo Community Health Center working area with a p value of 0.035 < 0 .05, There is no significant relationship between family support and exclusive breastfeeding behavior in the Meurebo Community Health Center Area with a p value of 0.730 > 0.05. The conclusion is that there is a significant relationship between education and knowledge and exclusive breastfeeding behavior in the working area of ​​the Meureubo Community Health Center. Then there is no significant relationship between family support and exclusive breastfeeding behavior in the working area of ​​the Meureubo Community Health Center.